XLUM: an open data format for exchange and long-term preservation of luminescence data - Kreutzer, Sebastian; Grehl, Steve; Höhne, Michael; Simmank, Oliver; Dornich, Kay; Adamiec, Grzegorz; Burow, Christoph; Roberts, Helen; Duller, Geoff (Geochronology, 2023)
The concept of open data has become the modern science meme, and major funding bodies and publishers support open data. On a daily basis, however, the open data mandate frequently encounters technical obstacles, such as a lack of a suitable data format for data sharing and long-term data preservation. Such issues are often community-specific and best addressed through community-tailored solutions. In Quaternary sciences, luminescence dating is widely used for constraining the timing of event-based processes (e.g. sediment transport). Every luminescence dating study produces a vast body of primary data that usually remains inaccessible and incompatible with future studies or adjacent scientific disciplines. To facilitate data exchange and long-term data preservation (in short, open data) in luminescence dating studies, we propose a new XML-based structured data format called XLUM. The format applies a hierarchical data storage concept consisting of a root node (node 0), a sample (node 1), a sequence (node 2), a record (node 3), and a curve (node 4). The curve level holds information on the technical component (e.g. photomultiplier, thermocouple). A finite number of curves represent a record (e.g. an optically stimulated luminescence curve). Records are part of a sequence measured for a particular sample. This design concept allows the user to retain information on a technical component level from the measurement process. The additional storage of related metadata fosters future data mining projects on large datasets. The XML-based format is less memory-efficient than binary formats; however, its focus is data exchange, preservation, and hence XLUM long-term format stability by design. XLUM is inherently stable to future updates and backwards-compatible. We support XLUM through a new R package xlum, facilitating the conversion of different formats into the new XLUM format. XLUM is licensed under the MIT licence and hence available for free to be used in open- and closed-source commercial and non-commercial software and research projects.
Gesehen am 04.06.2024